Effects of exercise mode on the peak oxygen uptake and blood lactate response in boys aged 11-12 years - Fabiana Andrade Machado; Luiz Antonacci Guglielmo; Camila Coelho Greco; Benedito Denadai (Universidade Federal de Santa Catarina, 2006)
The objective of this study was to analyze the effects of exercise mode (running x cycling) on the indexesrelated to aerobic fitness (VO2peak and blood lactate response to exercise) in children. Participated of this study 20 active boys apparently healthy (age = 11.48 + 0.41 yr.; body mass = 41.38 + 10.45 kg; stature = 147.45 + 6.56 cm), with sexual maturational level 1 and 2 (pubic hair), which performed two incremental tests, with stages of 3 minutes until voluntary exhaustion, in treadmill (TR) and cycle ergometer (CE), to the determination of peak oxygen uptake (VO2peak) and lactate threshold (LT). The VO2peak was determined through the higher value obtained at intervals of 15 seconds. The LT was determined as the exercise intensity where the first and sustained increase of blood lactate above rest level occurred. The VO2peak (45.16 + 5.98 x 42.93 + 7.51 ml/kg/min), maximal heart rate (196.5 + 6.98 x 187.3 + 9.27 bpm), VO2 at LL (31.82 + 10.09 x 25.19 + 7.36 ml/kg/min) and HR at LL (150.5 + 17.75 x 131.3 + 12.98 bpm) were significantly higher in TR than CE, respectively. Thus, similar to adults, boys of 11 to 12 years present higher aerobic indexes (submaximal and maximal) in running than cycling, which can haveimportant implications for healthy professionals that utilize exercise for the healthy promotion, rehabilitation and experimental designs. RESUMO O objetivo deste estudo foi analisar os efeitos do modo de exercício (corrida x ciclismo) sobre os índices relacionados com a aptidão aeróbia (VO2pico e resposta de lactato ao exercício) em crianças. Participaram doestudo 20 meninos, aparentemente saudáveis e ativos (idade = 11,48 + 0,41 anos; massa corporal = 41,38 + 10,45 kg; estatura = 147,45 + 6,56 cm), com níveis de maturação sexual 1 e 2 (pilosidade pubiana), que realizaram dois testes incrementais, com estágios de 3 minutos até a exaustão voluntária, em esteira rolante (ER) e bicicleta ergométrica (BE), para a determinação do pico do consumo de oxigênio (VO2pico) e do limiar de lactato (LL). O VO2pico foi determinado através do maior valor obtido em intervalos de 15 segundos. O LL foi determinado pelaintensidade de exercício que provocou o primeiro e sustentado aumento da concentração de lactato acima das concentrações de repouso. O VO2pico (45,16 + 5,98 x 42,93 + 7,51 ml/kg/min), freqüência cardíaca máxima (196,5 + 6,98 x 187,3 + 9,27 bpm), VO2 no LL (31,82 + 10,09 x 25,19 + 7,36 ml/kg/min) e FC no LL (150,5 + 17,75 x 131,3 + 12,98 bpm) foram significantemente maiores na ER do que na BE, respectivamente. Portanto, similar ao encontrado em adultos, meninos de 11 a 12 anos apresentam índices aeróbios (submáximos e máximos) maiselevados na corrida do que no ciclismo, o que pode ter importantes implicações para profissionais de saúde que utilizam o exercício físico para a promoção de saúde, reabilitação e delineamentos experimentais.